Factors discriminating inventory management performance: An exploratory study of Indian machine tool SMEs - Rajeev Narayana Pillai (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: There are many kinds of methods to evaluate the inventory management and economic performance of small and medium enterprises, but they still have some distinct shortcomings. In order to achieve a better evaluation result, we put forward a new model based on the evidences from developing country like India. Approach: This survey study, mainly based on the evidences from machine tool SMEs in India uses statistical methods to avoid the drawbacks of qualitative techniques. Findings: Through empirical data, it is established that "technology" is not the only concern, but other factors related to human resource, economic, organizational and behavioral aspects of SMEs are also vital in improving their IM performance. Originality: This study combines the role of factors such as managerial, technological, economical and contingency together for the first time in the context of SMEs.
Keywords: 650; inventory management; inventory management performance; machine tool; SMEs